SOME REGULATORY FRAMEWORK ON ENVIRONMENTAL POLLUTION IN NIGERIA - Okeokwo, ThankGod; Ojomachewu, Zekeri, Glory (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
Some regulations made under the powers of the National Environmental Standards and Regulations Enforcement Agency pursuant to its Act provides for Cleaner Production Technologies in most industries which have impact on air, water and plant existence within Nigeria. The Regulations have identified polluter pays principles and effective investment in up to date technologies as strategies to getting pollution free environment mould into environmental plans of new licensees in Pharmaceutical, soap, detergent and chemical related industries. Every person or body must ensure it does not contribute to the pollution of the environment beyond what the ecosystem can absorb. Pollution is the alteration of the natural use of environmental resources as to make it lose or change its natural, biological, chemical and physical essence beyond the capacity of the environment to absorb. There are activities which are contrary to natural existence of the environment but which does not distort the composition or nature of environmental resources. This article adopted doctrinal methodology and data sourced from regulations. It was found that environmental pollution may not be overcome by mere subsidiary legislation. It was recommended that enforcement of the Regulations plus synergy in areas of technical assistance and pollution remediation equipment acquisition and utilization among related agencies will go along-way at solving pollution issues around production facilities industries in Nigeria.